The Relationship Between Anxiety Levels And Knowledge Of Pregnant Women In Providing Antenatal Care (Anc) During The Covid-19 Pandemic At Hanna Kasih Clinic Pratama In 2022 - Emelia Apriani Tampubolon (International Journal of Medicine and Health, 2023)
A pregnant woman is a woman who is pregnant, starting from contraception until the birth of the fetus. The aim of ANC is to identify pregnancy complications that may occur during early pregnancy, to improve and maintain the health of the mother and baby. Covid-19 is a disease that attacks the respiratory system which has become an epidemic in Wuhan (China) which has spread throughout the world and has become a global pandemic. The research method is quantitative description. This research was conducted from January – July 2022. The population was 30 respondents, and the sample used an accidental sampling technique. The results of the distribution show that the majority age category is 20-35 years old, numbering 28 people (93.3%), the majority parity category for multiparas is 22 people (73.3%), the majority education category for high school education is 17 people (56, 7%), in the knowledge category the majority had sufficient and insufficient knowledge each amounting to 11 people (36.7%), and in the anxiety category the majority had no anxiety totaling 12 people (40%). The p-value for the level of anxiety was obtained at 0.014 and the p-value for the level of knowledge was 0.017 with ɑ (0.05), so it was concluded that there was a significant relationship between the level of knowledge and the level of anxiety regarding ANC visits during the Covid 19 pandemic at the Pratama Hana Kasih Clinic in 2022. It is hoped that mothers can increase awareness and vigilance during ANC visits at health facilities to reduce the risk of transmission of the Covid-19 virus.